A Bibliometric Analysis of Health and Medicine Research in Uganda - Kasule A; Mutebi B; Ssentumbwe A (Annals of Health Research, 2022)
Background: Research is one of the many domains that help countries to provide solutions to various challenges and improve facilities. The bibliometric analysis measures the research output of individuals/research teams, institutions, and countries and identifies national and international research networks across the globe.